'A monstrous threat': how a state of exception turns into a 'new normal'. Issue 7 (2nd August 2020) - Zinn, Jens O.
Abstract: This article explores the factors that helped COVID-19 to become a 'monstrous threat' to humanity, which legitimises significant restrictions to people's freedom and is justified by the ethics to keep everyone safe. It analyses how rigid means increase old inequalities and produce secondary risks and significant side-effects and demonstrates how, with social and economic costs soaring, governments seek ways back – not to the old normal – but new social practices and attitudes towards infectious diseases, thereby transforming the state of exception into a 'new normal'.